Impact of Product Variety on Repurchase Decisions: The Mediating Role of Customer Satisfaction - Wafi Ega Bhagaskara; Muslikh (SAN Scientific, 2026)
This study aims to analyze the influence of product variation on repurchase decisions for Woven Coffee products, with customer satisfaction serving as a mediating variable. The research employed a quantitative approach, with 90 respondents selected through purposive sampling, and data collected via questionnaires. The data were analyzed using the Partial Least Squares (PLS) method. The results indicate that product variation has a positive and significant effect on customer satisfaction, and customer satisfaction positively and significantly influences repurchase decisions. Moreover, product variation directly has a positive and significant impact on repurchase decisions, whereas customer satisfaction does not mediate this relationship. These findings suggest that customers are more likely to make repeat purchases when they perceive a high level of product variety, regardless of satisfaction mediation. The managerial implications emphasize the importance of developing innovative, diverse product assortments to attract and retain customers, as well as of improving the customer experience to enhance loyalty. Future research is recommended to include additional variables and a larger sample to understand better the factors influencing repurchase behavior.